Pengaruh Penggunaan Papan Pintar Literasi terhadap Pemahaman Struktur Kalimat dalam Pembelajaran Bahasa Indonesia di Sekolah Dasar - Quswatun Qasanah; Sri Jumani; Siti Kuttomah (Universitas Muria Kudus, 2025)
This study investigates the effectiveness of the Literacy Smart Board as an interactive learning medium to improve students’ understanding of sentence structure in Indonesian language learning at the elementary school level. The research addresses an educational challenge commonly found in early-grade classrooms, namely students’ limited comprehension of basic sentence components due to predominantly conventional and teacher-centered instructional practices. The study was conducted with 33 second-grade students at SD Negeri 2 Banjarejo using a descriptive qualitative approach, supported by quantitative data obtained from pre- and post-learning assessments. Data collection techniques included classroom observation, documentation of students’ learning outcomes, and analysis of learning activities during the implementation of the Literacy Smart Board. The findings reveal that prior to the intervention, 13 students (39.4%) experienced difficulties in identifying sentence elements such as subjects, predicates, and objects. After the use of the Literacy Smart Board, the number of students with learning difficulties decreased to 3 students (9.1%), indicating an improvement of 30.3% in students’ understanding of sentence structure. These results demonstrate that the interactive, visual, and concrete features of the Literacy Smart Board significantly enhance student engagement, learning motivation, and grammatical comprehension. This study contributes to the field of educational technology by providing empirical evidence on the effective use of interactive literacy media in primary education. Moreover, the findings offer practical implications for teachers, particularly in rural or resource-limited schools, by presenting an accessible instructional innovation to improve Indonesian language learning outcomes.